An experimental analysis of quenching of continuously heated vertical rod with aqueous Al2O3 nanofluid; Resource-Efficient Technologies; Vol. 3, iss. 4 - Nirupama Patraa; Vivek Guptab; Ravi Singhb; Singha R. S.; Pradyumna Ghoshb; Arun Nayakc (2017, 2017)
Title screen